Novas perspectivas da análise estratégica: estudo de caso do UOL: como o caso do Universo On Line (UOL) pode criar novas perspectivas para a análise estratégica? - Baumgart, Christian (2001)
Study of the challenges and new strategic perspectives to be faced with the UOL case - Universo On Line -leader Internet Service Provider and Portal in Brazil, based on facts and statistics of the market and interview with the UOL.